Palladium nanoparticle-modified carbon nanotubes for electrochemical hydrogenolysis in ionic liquids - Meng, Y; Aldous, L; Pilgrim, B; Donohoe, T; Compton, R (2011)
The electrochemical hydrogenolysis of benzyl and carboxybenzyl protecting groups is described. Optimisation of a synthetic protocol afforded well-defined palladium (Pd) nanoparticles on the surface of multiwall carbon nanotubes (CNTs). The high surface area composite was investigated, and differences observed in the voltammetry for the same composite in aqueous and ionic liquid systems are discussed. When used to reduce acidic protons in the ionic liquid (IL) 1-ethy-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C 2mim][NTf2]) reactive palladium hydride was formed efficiently, which rapidly performed hydrogenolysis. The compounds 1-(3-(benzyloxy)propyl)-4-methoxybenzene, benzyl octyl carbonate, N,N′-bis(benzyloxycarbonyl)-l-lysine and N-benzyl-l-prolinol were investigated. Extended electrolysis of bis(trifluoromethylsulfonyl)imide (H[NTf2]) in [C2mim][NTf2] containing alcohol groups protected with benzyl and carboxybenzyl groups afforded the alcohol product in high yield. The probable hydrogenolysis of the similarly protected amine groups is also reported. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.